Prognostic significance of ASXL1 mutations in myelodysplastic syndromes and chronic myelomonocytic leukemia: A meta-analysis. Issue 8 (13th September 2016) - Lin, Yun; Zheng, Yi; Wang, Ze-Chuan; Wang, Shao-Yuan
Abstract : Objectives : Although additional sex comb-like 1 ( ASXL1 ) gene mutations have long been reported in myelodysplastic syndromes (MDSs) and chronic myelomonocytic leukemia (CMML), the prognostic significance has been controversial. Therefore, a meta-analysis to study the impact of ASXL1 mutations on patients with MDS and CMML is useful. Methods : The identified articles were retrieved from some common databases. We extracted hazard ratios (HRs) for overall survival (OS) and leukemic-free survival (LFS) and P -value of some clinical parameters, which compared AXSL1 mutations to those without from the available studies. Each individual HR and P -value was used to calculate the pooled HR and P -value. Results : Six studies covering 1689 patients were selected for this meta-analysis. The pooled HRs for OS and LFS were 1.45 (95% confidential interval (CI), 1.24–1.70) and 2.20 (95% CI, 1.53–3.17), respectively. When considering CMML patients alone the HR for OS was 1.50 (95% CI, 1.18–1.90). Additionally, ASXL1 mutations were more frequently found in male ( P  = 0.008), older ( P  = 0.019), and patients with lower platelets ( P  = 0.009) or hemoglobin level ( P  = 0.0015) and associated with other mutations such as EZH2, IDH1/2, RUNX1, and TET2 . Discussion : Although our analysis has its limitation, it showed that ASXL1 mutations had significant inferior impact on OS and LFS for French–American–British-defined MDS patients. However, the influence of different types of ASXL1 mutations on patients with MDS still needs illustrating. Conclusion : ASXL1 mutations were associated with poor prognosis in MDS, which may contribute to risk stratification and prognostic assessment in the disease.